Transdermal Estrogen Therapy Improves Gains in Skeletal Muscle Mass After 12 Weeks of Resistance Training in Early Postmenopausal Women - Dam, Tine Vrist; Dalgaard, Line Barner; Ringgaard, Steffen; Johansen, Frank Ted; Bisgaard Bengtsen, Mads; Mose, Maike; Lauritsen, Katrine Meyer; Ørtenblad, Niels; Gravholt, Claus H.; Hansen, Mette (Frontiers in Physiology, 2021)
Context. Women show an accelerated loss of muscle mass around menopause, possibly related to the decline in estrogen. Furthermore, the anabolic response to resistance exercise seems to be hampered in postmenopausal women. Objective. We aimed to test the hypothesis that transdermal estrogen therapy amplify the skeletal muscle response to resistance training in early postmenopausal women. Design. Double-blinded randomized study. Setting. Department of Public Health, Aarhus University, Denmark. Participants. Thirty-one healthy, untrained postmenopausal women no more than 5 years past menopause. Intervention(s). Supervised resistance training with placebo (PLC, n=16) or transdermal estrogen therapy (ET, n=15) for 12 weeks. Main Outcome Measure(s). The primary outcome parameter was cross sectional area of quadriceps femoris measured by magnetic resonance imaging, and secondary parameters were fat free mass (DXA), muscle strength and functional tests. Results. The increase in muscle cross sectional area was significantly greater in the ET group (7.9%) compared to the PLC group (3.9%) (p<0.05). Similarly, the increase in whole body fat free mass was greater in the ET group (5.5%) than in the PLC group (2.9%)(p<0.05). Handgrip strength increased in ET (p<0.05), but did not change in the PLC group. Muscle strength parameters, jumping height and finger strength were all improved after the training period with no difference between groups. Conclusion: Use of transdermal estrogen therapy enhanced the increase in muscle mass in response to 12 weeks of progressive resistance training in early postmenopausal women.